Dissemination, Abundance Rates and Epizootiological Significance of the Tick Dermacentor reticulatus in the Territory of the Tula Region - T. V. Kozlova; A. S. Ignat’kova; E. M. Dorofeev; V. P. Popov; D. S. Orlov (Проблемы особо опасных инфекций, 2016)
Objective of the study is to summarize long-term data on the dynamics of areal and abundance rates of the prairie tick, D. reticulatus in the territory of the Tula Region. Materials and methods. Processed and reviewed have been literature sources, archive documents, and results of personal observations over a period of 1949–2013. Applied have been computer-based software products Google Earth, MapInfo Professional v. 11.5. wrapped in GIS Software Package. Results and conclusions. It is determined that over the last decade D. reticulatus has been found not only in the forest and adjacent western forest-steppe zone, but also in the eastern and south-eastern forest-steppe area. Specified have been the territories with uniformly high density of population and sparse distribution of D. reticulatus ticks. It is established that nowadays abundance rates of the ticks show no substantial differences both in the forestmeadow areas of the forest zone, and similar areas of the forest-steppe zone. Identified has been correlation between the nature of F. tularensis culture isolation from D. reticulatus and intensity of epizootic process of tularemia infection, which allows for in-time targeted epizootiological survey and regulation of preventive activities.